2023
DOI: 10.1088/2515-7620/acb90b
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected high contribution of in-cloud wet scavenging to nitrogen deposition induced by pumping effect of typhoon landfall in China

Abstract: Atmospheric nitrogen deposition has large eco-environmental effects such as ocean acidification, eutrophication in coastal areas. However, knowledge of the source and the pathway of N deposition in coastal areas is limited, especially during tropical storms, hindering the accurate quantification of how anthropogenic activities influence the ocean ecosystem. In this study, the Nested Air Quality Prediction Modeling System was used to investigate the wet deposition of N induced by typhoon Hagupit over eastern co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Typhoons are usually associated with hazards, such as strong winds, storm surges, and rainfall, that can cause considerable damage and disruption. Although such a strong wind field could simply result in good ventilation and reduce air pollutant concentrations, several studies have reported that typhoons degraded air quality in terms of PM 2.5 17 , 18 , O x 19 , 20 , and deposition 21 , 22 . Because the O x warning issued in September 2020 occurred in a remote area of Goto Island, westernmost Nagasaki Prefecture, the horizontal distribution over East Asia should also be examined.…”
Section: Resultsmentioning
confidence: 99%
“…Typhoons are usually associated with hazards, such as strong winds, storm surges, and rainfall, that can cause considerable damage and disruption. Although such a strong wind field could simply result in good ventilation and reduce air pollutant concentrations, several studies have reported that typhoons degraded air quality in terms of PM 2.5 17 , 18 , O x 19 , 20 , and deposition 21 , 22 . Because the O x warning issued in September 2020 occurred in a remote area of Goto Island, westernmost Nagasaki Prefecture, the horizontal distribution over East Asia should also be examined.…”
Section: Resultsmentioning
confidence: 99%